Synthesis and characterization of simple cost-effective trans-A(2)BC porphyrins with various donor groups for dye-sensitized solar cells - Kumar, Ravi; Sankar, Muniappan; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (New Journal of Chemistry, 2016)
We have designed and synthesized a series of simple cost-effective 'push-pull' Zn(II) porphyrin dyes containing various electron donors such as 2-thienyl, pyrenyl, phenyl, 4'-bromophenyl, 4'-tbutylphenyl and 4'-carboxyphenyl acceptor moieties in three steps. Their optical absorption spectra, electrochemical redox and photovoltaic properties have been investigated in detail. The overall power conversion efficiencies (Z) of DSSCs based on these dyes are in the range of 2.1 to 4.2% and highly depend on their donor moiety. The incorporation of trans-10,20-dimesityl groups is highly beneficial for preventing the p-p aggregation among the porphyrin moieties, thus favorably suppressing the charge recombination and intermolecular interaction. Among all, pyrenyl appended Zn(II) porphyrin has exhibited a higher power conversion efficiency of 4.2% under 1 sun illumination due to the extended p-conjugation and electron donating ability of the pyrenyl moiety.

Silk cocoon as counter - electrode substrate in dye - sensitized solar cells - Sudhakar, Vediappan; Das, Chayanika; Krishnamoorthy, Kothandam (ChemistrySelect, 2018)
Electrodes are vital components of energy conversion devices such as dye sensitized solar cells (DSSCs). The widely used electrodes consist of fluorine doped tin oxide (FTO) and platinum. We were interested in identifying a substrate that is available from natural resources and exhibit performance comparable to that of Pt coated FTO (Pt-FTO). Silk fibers are naturally available and they are mechanically stable. The woven silk fibers are known as silk cocoons (SCs) that structurally resemble widely used carbon paper electrodes. To impart conductivity to the insulating SCs, metal film was coated by an electroless metal plating procedure using polyphenols from green tea. The metal coated SCs were conformaly coated with a conjugated polymer and these electrodes were used as flexible electrodes in DSSCs. The flexible electrode based DSSCs exhibited a power conversion efficiency of 7.2% which is comparable to that of the DSSCs with rigid Pt-FTO based devices (7.4%).
Keywords: counter electrode; PEDOT-G-SCs; Recombination; Silk cocoons (SCs)